Unraveling Hepatic Metabolomic Profiles and Morphological Outcomes in a Hybrid Model of NASH in Different Mouse Strains - Bacil, Gabriel P. [UNESP]; Romualdo, Guilherme R. [UNESP]; Piagge, Priscila M. F. D.; Cardoso, Daniel R.; Vinken, Mathieu; Cogliati, Bruno; Barbisan, Luís F. [UNESP] (MDPI, 2023)
Nonalcoholic fatty liver disease (NAFLD) encompasses nonalcoholic steatohepatitis (NASH) and affects 25% of the global population. Although a plethora of experimental models for studying NASH have been proposed, still scarce findings regarding the hepatic metabolomic/molecular profile. In the present study, we sought to unravel the hepatic metabolomic profile of mice subjected to a hybrid model of NASH, by combining a Western diet and carbon tetrachloride administration, for 8 weeks, in male C57BL/6J and BALB/c mice. In both mouse strains, the main traits of NASH—metabolic (glucose intolerance profile), morphologic (extensive microvesicular steatosis and fibrosis, lobular inflammation, and adipose tissue-related inflammation/hypertrophy), and molecular (impaired Nrf2/NF-κB pathway dynamics and altered metabolomic profile)—were observed. The hepatic metabolomic profile revealed that the hybrid protocol impaired, in both strains, the abundance of branched chain-aromatic amino acids, carboxylic acids, and glycosyl compounds, that might be linked to the Nrf2 pathway activation. Moreover, we observed a strain-dependent hepatic metabolomic signature, in which the tricarboxylic acid metabolites and pyruvate metabolism were dissimilarly modulated in C57BL/6J and BALB/c mice. Thus, we provide evidence that the strain-dependent hepatic metabolomic profile might be linked to the distinct underlying mechanisms of NASH, also prospecting potential mechanistic insights into the corresponding disease.
Keywords: carbon tetrachloride; metabolomic profile; nonalcoholic fatty liver disease; nonalcoholic steatohepatitis; western diet